Investigation on the pollen morphology of traditional cultivars of Prunus species in Sicily - Anna Geraci; Vincenza Polizzano; Pasquale Marino; Rosario Schicchi (Acta Societatis Botanicorum Poloniae, 2012)
In this study pollen grains of 13 cultivars and 3 rootstocks belonging to 5 species (P. armeniaca, P. domestica, P. dulcis, P. persica, P. avium) of the genus Prunus collected from North-East Sicily were examined for the micromorphological characterization through the scanning electron microscopy (SEM). The length of polar axis (P) and the equatorial diameter (E) of grain, P/E ratio, the length of colpi (C), diameter of perforations (DP) and the number of perforations in 25 μm2 (PN), the width of muri (WM), the distance between muri (DM) and their number in 25 μm2 (MN), the width of grooves (WG) were measured and their variation was compared among studied taxa. Moreover multivariate statistical analysis was carried out to distinguish morphometric information from measured parameters. All pollen grains are trizonocolpate, isopolar, medium-large sized and their shape varies from prolate to perprolate. Regarding outline pollen grains are subtriangular in polar view and elliptic in equatorial view. Exine sculpturing is striate with perforations on grain surface. The arrangement of ridges appears roughly parallel but too sloped (sometimes curved) compared to polar axis, or branched and oriented in different directions, or perfectly parallel or more irregular with bifurcated ridges often sinuous. The analyses showed a great variability (particularly in P. domestica cultivars) related in some cases to the diversity in the morphological features of the leaves and the fruits of the investigated entities.